Reflection of Political Struggle in Italy in Documents of Communist International (1919—1923) - E. N. Emelyanova (Научный диалог, 2024)
The article examines the events that unfolded in Italy between 1919 and 1923. Based on a large number of documents, archival sources, and literature, it explores the fierce struggle between socialists, communists, on one side, and fascists on the other, which culminated in Benito Mussolini’s victory in 1922. The article analyzes the theoretical understanding of fascism as a phenomenon by the communists, as well as the development of methods to combat it, which were reflected in the congresses of the Communist International and the plenums of its Executive Committee from 1919 to 1923. The novelty of the research lies in addressing the issue of confrontation between left and far-right parties after World War I, during the formation of a new world order. The author concludes that the intensification of the struggle between the Communist Party of Italy, the Socialist Party of Italy, and fascism reflected a political crisis in Italian society and an attempt by radical forces to find a way out of it. Fascism, with its idea of a third way representing something between capitalism and socialism, came to power in Italy. The realization of their mistakes ultimately allowed the left parties to unite with all anti-fascist forces in the Resistance movement and defeat Nazism during World War II.